Digital Technology Use Patterns in History Education: A Case Study of Autonomous Public Schools in Cambodia - Vuthy Khorn; Kimkong Heng (Journal of Education Research, 2026)
Digital technology integration in education has grown rapidly, yet research in Cambodia remains concentrated on STEM subjects, leaving social sciences and humanities—particularly history—underexplored. This study aims to examine how history teachers introduce, adapt, and incorporate digital technology into lessons, identifying current challenges and best practices from their perspectives. Using a qualitative design, in-depth interviews of 40 minutes were conducted with 10 purposively selected high school history teachers from two Autonomous Public Schools in Phnom Penh between November and December 2024. Data were analyzed thematically using MAXQDA 24. Findings reveal that teachers' digital competencies were strengthened through mandatory foundation workshops and ongoing professional development within a Professional Learning Community facilitating mentorship and peer learning. Most teachers employed digital tools to enhance administrative efficiency and support historical research. Despite challenges including technological obsolescence, language barriers, and STEM-oriented resource allocation, the majority demonstrated positive attitudes toward digital integration, fostering professional growth and enriching student learning through innovative teaching practices.